Feedback-Based Control for Providing Real-Time Services With the 802.11e MAC - Gennaro Boggia; Pietro Camarda; Luigi Grieco; Saverio Mascolo (IEEE/ACM Transactions on Networking, 2007)
The 802.11e working group has recently proposed the hybrid coordination function (HCF) to provide service differentiation for supporting real-time transmissions over 802.11 WLANs. The HCF is made of a contention-based channel access, known as enhanced distributed coordination access, and of a HCF controlled channel access (HCCA), which requires a Hybrid Coordinator for bandwidth allocation to nodes hosting applications with QoS requirements. The 802.11e proposal includes a simple scheduler providing a Constant Bit Rate service, which is not well suited for bursty media flows. This paper proposes two feedback-based bandwidth allocation algorithms to be used within the HCCA, which have been referred to as feedback based dynamic scheduler (FBDS) and proportional-integral (PI)-FBDS. These algorithms have been designed with the objective of providing services with bounded delays. Given that the 802.11e standard allows queue lengths to be fed back, a control theoretic approach has been employed to design the FBDS, which exploits a simple proportional controller, and the PI-FBDS, which implements a proportional-integral controller. Proposed algorithms can be easily implemented since their computational complexities scale linearly with the number of traffic streams. Moreover, a call admission control scheme has been proposed as an extension of the one described in the 802.11e draft. Performance of the proposed algorithms have been theoretically analyzed and computer simulations, using the ns-2 simulator, have been carried out to compare their behaviors in realistic scenarios where video, voice, and FTP flows, coexist at various network loads. Simulation results have shown that, unlike the simple scheduler of the 802.11e draft, both FBDS and PI-FBDS are able to provide services with real-time constraints. However, while the FBDS admits a smaller quota of traffic streams than the simple scheduler, PI-FBDS allows the same quota of traffic that would be admitted using the simple scheduler, but still providing delay bound guarantees
Keywords: Pi control; Traffic control; Channel allocation; Algorithm design and analysis; Delay; Proportional control; Streaming media; Computer simulation; Computational modeling; Telecommunication traffic; Real-time applications; QoS; wireless networks